An Introduction to the IBMR : A Hydro-Economic Model for Climate Change Impact Assessment in Pakistan’s Indus River Basin - Yang, Yi-Chen E. (Taylor and Francis, 2013)
The Indus Basin Model Revised (IBMR) is a hydro-agro-economic optimization model for agricultural investment planning across Pakistan’s Indus Basin provinces. This study describes IBMR-2012, an update and modification of the model that reflects the current agro-economic conditions in Pakistan for the purpose of evaluating the impact of climate change on water allocation and food security. Results of hydro-climatic parameter sensitivity and basin-wide and provincial-level climate change impacts on crop productions are presented. The study finds that compared to Punjab, Sindh faces both significantly larger climate change impacts on agriculture and higher uncertainty regarding climate change impacts in the future.